Pembentukan Peer group Sebagai Edukator Donor Darah Untuk Peningkatan Donor Sukarela pada Kelompok Remaja - Yuli Astuti (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2022)
Blood service is an activity that starts from the recruitment and selection of donors, blood collection, blood safety, processing of blood components, and blood distribution. Teenagers as one of the targets of donor recruitment need to provide good information and education, peer groups are a good tool to use for students. Objective of this community service is to disseminate information about safe blood donation to adolescents, and to establish peer groups as blood donor educators. Methode the implementation of this activity is planned in stages, namely: the preparation stage, and the implementation stage. The preparation stages include obtaining permits, preliminary studies with field observations, collecting materials and preparing tools and materials during activities as well as coordinating with related parties. The stages of implementing the activity are conducting socialization about safe blood donors for adolescents, and the formation of peer groups as blood donor educators. Results of this community service there is an increase in knowledge before and after being given socialization from those with less knowledge with a percentage of 15.07% decreasing to 6.12% and those with good knowledge from (17.87%) increasing to (28.57%). Based on community services is that there is an increase in knowledge before and after being given socialization.